The Relationship Between Metacognitive Ability and Self-directed Learning of Chemistry Education Students as Prospective Teacher - Candrawinata, Natalia; Erlina, Erlina; Ulfah, Maria (Hydrogen: Jurnal Kependidikan Kimia, 2024)
Metacognitive ability and self-directed learning are crucial aspects to consider because good metacognitive skills are closely linked to academic success and self-directed learning. Students with strong metacognitive abilities are generally more capable of planning, monitoring, and evaluating their learning activities effectively. This study utilized a descriptive quantitative method with a correlational approach to examine the relationship between two variables: metacognitive ability and self-directed learning. The research was conducted in the Chemistry Education Program at FKIP Untan, focusing on 51 sixth-semester students for the academic year 2023/2024. Data were collected through indirect communication methods using the MAIT-18 and a self-directed learning questionnaire. The data analysis used descriptive statistical methods. The results indicated that the percentages of metacognitive ability and self-directed learning among sixth-semester Chemistry Education students were 79% and 68%, respectively. The Spearman Rank correlation test revealed a significance value of 0.478 >Â  0.05. Therefore, H0 is accepted and Ha is rejected, indicating that there is no significant relationship between metacognitive ability and self-directed learning among the students of the Chemistry Education Program at FKIP Untan.